Placenta percreta complicated by uterine rupture and thrombotic microangiopathy - Laužikienė, Dalia; Vosylius, Saulius; Šiaudinytė, Ieva; Laužikas, Emilis; Ramašauskaitė, Diana; Bartkevičienė, Daiva (Acta medica Lituanica, 2018)
Background. Uterine rupture at the site of a previous caesarean scar with abnormal placental penetration through the uterus wall with bladder invasion is a rare and serious pregnancy complication. Our aim was to report a case of uterine rupture with placenta percreta complicated by thrombotic microangiopathy. Materials and methods. We did a literature review and analysed medical documentation retrospectively. Results. A patient was admitted with complaints of lower abdominal pain at 21 weeks of gestation. Sonography of the caesarean scar increased suspicion of placental penetration. Anaemia, thrombocytopenia, coagulopathy, and acute kidney injury developed and led to the diagnosis of thrombotic microangiopathy. The termination of pregnancy was required due to severe deterioration in organ functions. The complete uterine rupture with placenta percreta invading the urinary bladder was confirmed, and total hysterectomy was performed to control life-threatening haemorrhage. The patient was treated by blood component transfusions, renal replacement therapy, and plasmapheresis. Good health was confirmed two months later by laboratory and instrumental tests. Conclusions. It is a rare but very serious condition that increases morbidity of mother and foetus, therefore immediate diagnostics and treatment are required.
Keywords: placenta percreta; thrombotic microangiopathy; uterine rupture; acute kidney injury; blood component transfusion